Free electron laser infrared action spectroscopy of nitrous oxide binding to platinum clusters, Ptn(N2O)+. Issue 33 (12th August 2020) - Meizyte, Gabriele; Green, Alice E.; Gentleman, Alexander S.; Schaller, Sascha; Schöllkopf, Wieland; Fielicke, André; Mackenzie, Stuart R
Abstract : Infrared multiple-photon dissociation spectroscopy has been applied to study Pt n (N2 O) + ( n = 1–8) clusters which represent entrance-channel complexes on the reactive potential energy surface for nitrous oxide decomposition on platinum. Abstract : Infrared multiple-photon dissociation spectroscopy has been applied to study Pt n (N2 O) + ( n = 1–8) clusters which represent entrance-channel complexes on the reactive potential energy surface for nitrous oxide decomposition on platinum. Comparison of spectra recorded in the spectral region 950 cm −1 to 2400 cm −1 with those simulated for energetically low-lying structures from density functional theory shows a clear preference for molecular binding via the terminal N atom, though evidence of O-binding is observed for some cluster sizes. Enhanced reactivity of Pt n + n ≥ 6 clusters towards N2 O is reflected in the calculated reactive potential energy surfaces and, uniquely in the size range studied, Pt6 (N2 O) + proved impossible to form in significant number density even with cryogenic cooling of the cluster source. Infrared-driven N2 O decomposition, resulting in the formation of cluster oxides, Pt n O +, is observed following vibrational excitation of several Pt n (N2 O) + complexes.